1980
DOI: 10.1111/j.1600-0528.1980.tb01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of traumatized permanent anterior teeth to occlusion and lip condition

Abstract: A comparative epidemiologic study on traumatized permanent anterior teeth was conducted on 6090 Iraqi and 3507 Sudanese primary schoolchildren. A significant relationship was found between the severity of trauma to protrusion of maxillary incisors and amount of lip coverage in Iraqis and a similar tendency was observed for the Sudanese. In a comparison between the two population groups the frequency of traumatized permanent maxillary incisors with greater tooth loss (types 3 + 4) were significantly higher in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 4 publications
3
12
0
2
Order By: Relevance
“…The incidence of trauma in this study was similar to that reported for Nigerians (6) and Syrians (18) but a little higher than that for Iraqi and Sudanese (11). In the latter study, the incidence of trauma to anterior teeth was 7.7 and 5.1% in Iraqi and Sudanese children respectively.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of trauma in this study was similar to that reported for Nigerians (6) and Syrians (18) but a little higher than that for Iraqi and Sudanese (11). In the latter study, the incidence of trauma to anterior teeth was 7.7 and 5.1% in Iraqi and Sudanese children respectively.…”
Section: Discussionsupporting
confidence: 86%
“…While there is clear evidence of an association between size of overjet and TDI, there is limited evidence whether anterior open bite is related to the occurrence of TDI. Similarly, there are few reports on the relationship between malocclusion traits and the occurrence of TDI to the primary teeth (16–18) compared to large number of studies assessing this association in the permanent dentition (7, 16–20).…”
Section: The Prevalence Of Dental Injuries In Preschool Children; Sumentioning
confidence: 99%
“…relationship between malocclusion traits and the occurrence of TDI to the primary teeth (16)(17)(18) compared to large number of studies assessing this association in the permanent dentition (7,(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Forsberg & Tedestam [16] described a greater average overjet in patients with more severe injuries, such as fractures involving root injuries or avulsions, than in cases of simple enamel fractures, and Schnyder & Eicke [30] also showed a clear increase in the percentage of more severe injuries as overjet increased. Ghose et al [17] also highlighted an increase in the severity of incisor trauma when lip coverage is inadequate. This is corroborated by our results in this study.…”
Section: Diskussionmentioning
confidence: 99%